Preparation method and application of graphene quantum dot composite electrolytic water oxygen evolution catalytic material

By loading Fe-Ni(OH)2 on the surface of nickel foam and electrodepositing Co(OH)2, and then electrodepositing graphene quantum dots on the composite oxygen evolution catalytic material, a graphene quantum dot composite electrolysis water oxygen evolution catalytic material was prepared , which solves the problems of high cost of noble metal-based catalytic materials and insufficient catalytic activity of non-noble metals, and achieves efficient and low-cost OER electrocatalytic performance.

CN119320963AActive Publication Date: 2025-01-17YANAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411444930.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-17
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The existing precious metal-based electrolytic oxygen-induced catalytic materials have high cost, while the catalytic activity of OER electrocatalytic materials that are not precious metals needs to be improved.

Method used

The preparation method of graphene quantum dot composite oxygen evolution catalytic material for water electrolysis is adopted, by loading Fe-Ni(OH)2 on the surface of nickel foam, and electrodepositing Co(OH)2 on it, and finally on the composite oxygen evolution catalytic material. Graphene quantum dots are electrodeposited to form a graphene quantum dot composite electrolysis water oxygen evolution catalytic material.

Benefits of technology

A noble metal-free OER electrocatalytic material has been realized with low cost and excellent electrocatalytic water separation activity. It only needs 238mV to drive a current density of 100mA/cm2, with a Tafel slope of 85mV/dec, showing a high OER electrocatalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320963A_ABST
    Figure CN119320963A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a graphene quantum dot composite electrolytic water oxygen evolution catalytic material, and aims to solve the problem that the activity of an OER electrocatalytic material without noble metal needs to be improved. The preparation method comprises the following steps: 1, ultrasonically cleaning foamed nickel; 2, preparing a graphene quantum dot solution; 3, nickel chloride hexahydrate, ferric nitrate nonahydrate, urea and ammonium fluoride are dissolved in deionized water, a reaction solution is obtained, and foamed nickel is placed in the reaction solution for a hydrothermal reaction; 4, the foam nickel loaded with Fe-Ni (OH) 2 is placed in a Co (OH) 2 aqueous solution, and constant-potential electro-deposition is carried out; and 5, immersing the Co (OH) 2-Ni (OH) 2 / foamed nickel into the graphene quantum dot solution, and carrying out electro-deposition by adopting cyclic voltammetry to obtain the oxygen evolution catalytic material. The composite electrolytic water oxygen evolution catalytic material contains three transition metal elements of iron, cobalt and nickel, graphene quantum dots are electrically deposited on the surface of the composite electrolytic water oxygen evolution catalytic material, and the composite electrolytic water oxygen evolution catalytic material shows good electro-catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a Co(OH)2-Ni(OH)2 / foamed nickel composite water electrolysis oxygen evolution catalytic material. Background Art

[0002] With the intensification of energy crisis and environmental pollution, it is crucial to develop efficient and environmentally friendly new energy conversion and storage technologies. Water electrolysis is considered to be an efficient hydrogen production method due to its abundant raw materials, high product purity, environmental protection and sustainability. The reaction consists of two parts: cathode hydrogen evolution reaction and anode oxygen evolution reaction.

[0003] The oxygen evolution reaction is a complex four-electron reaction process that requires a high overpotential. In the process of water electrolysis, OER exhibits slow reaction kinetics. Precious metal catalysts such as rubidium, iridium, and platinum-based catalysts are currently widely considered to be efficient OER catalysts, but precious metal catalysts are not suitable for large-scale industrial applications due to their high prices.

[0004] The application of non-precious metal materials in electrocatalysis is becoming more and more extensive. For example, transition metal catalysts have shown good performance in electrocatalysis, among which transition metal oxides or hydroxides have good OER catalytic activity. However, the poor conductivity of pure oxides limits the further improvement of the catalytic performance of the materials. Summary of the invention

[0005] The purpose of the present invention is to solve the problem that the cost of existing noble metal-based water electrolysis oxygen evolution catalytic materials is high and the catalytic activity of OER electrocatalytic materials without noble metals needs to be improved, and to provide a preparation method and application of a graphene quantum dot composite water electrolysis oxygen evolution catalytic material.

[0006] The preparation method of the graphene quantum dot composite water electrolysis oxygen evolution catalytic material of the present invention is achieved by the following steps:

[0007] Step 1, ultrasonically cleaning the nickel foam (NF) with hydrochloric acid, acetone, anhydrous ethanol, and deionized water in sequence, and obtaining the cleaned nickel foam after drying;

[0008] Step 2: ultrasonically disperse graphene oxide in deionized water, add 30% H2O2 by mass, heat and reflux for 15 to 20 hours, and then dialyze through a 3500Da dialysis bag to obtain a graphene quantum dot (GODs) solution;

[0009] Step 3, dissolving nickel chloride hexahydrate, ferric nitrate nonahydrate, urea and ammonium fluoride in deionized water to obtain a reaction solution, placing the cleaned nickel foam in the reaction solution, and performing a hydrothermal reaction at a temperature of 120 to 150° C. for 6 to 10 hours to obtain a nickel foam loaded with Fe-Ni(OH)2;

[0010] Step 4: placing the nickel foam loaded with Fe-Ni(OH)2 in a Co(OH)2 aqueous solution, and using a three-electrode system to perform constant potential electrodeposition at -0.7 to -0.9 V to obtain Co(OH)2-Ni(OH)2 / nickel foam;

[0011] Step 5: immerse Co(OH)2-Ni(OH)2 / nickel foam as a working electrode in a graphene quantum dot solution, perform electrodeposition in a scanning potential window of 0V to 1.0V using cyclic voltammetry, and obtain a graphene quantum dot composite electrolytic water oxygen evolution catalytic material after washing and drying;

[0012] The molar ratio of nickel chloride hexahydrate to ferric nitrate nonahydrate in the reaction solution of step 3 is (8-15):(1-4).

[0013] The application of the graphene quantum dot composite water electrolysis oxygen evolution catalytic material of the present invention is to apply the graphene quantum dot composite water electrolysis oxygen evolution catalytic material as an OER electrocatalyst in the electrocatalytic water decomposition reaction.

[0014] The present invention prepares a Co(OH)2-Ni(OH)2 composite oxygen evolution catalytic material loaded with graphene quantum dots on the surface of nickel foam, uses nickel foam as a substrate, loads Fe-Ni(OH)2 on the substrate by a hydrothermal method, and changes the local electronic structure of Ni(OH)2 by Fe ion doping, thereby improving the conductivity of iron-nickel hydroxide and reducing the starting potential of OER. Co(OH)2 is electrodeposited on the nickel foam loaded with Fe-Ni(OH)2, so that the composite oxygen evolution catalytic material contains three transition metal elements of iron, cobalt and nickel, and Co(OH)2 and Ni(OH)2 have good OER activity but relatively insufficient conductivity. Iron, cobalt and nickel can enhance electron transfer to each other, promote active centers, and disperse Co(OH)2 particles. Finally, graphene quantum dots are electrodeposited on the composite oxygen evolution catalytic material. Graphene quantum dots have high electrocatalytic activity and excellent electrical conductivity, which ensures the rapid transfer of ions / electrons and strengthens the transfer of electrons from metal active centers to quantum dots. At the same time, the edge sites of graphene quantum dots can promote reaction kinetics, thereby improving the OER activity of the composite water electrolysis oxygen evolution catalytic material.

[0015] The preparation method of the graphene-based composite water electrolysis oxygen evolution catalytic material of the present invention has the following beneficial effects:

[0016] 1. The graphene quantum dot composite electrolytic water oxygen evolution catalytic material prepared by the present invention is applied to the electrocatalytic decomposition of water and oxygen evolution reaction. The composite electrolytic water oxygen evolution catalytic material does not contain precious metal elements, has low cost, simple synthesis method, and the electrodeposition method improves the stability of the composite oxygen evolution catalytic material;

[0017] 2. The graphene quantum dot composite electrolytic water oxygen evolution catalytic material prepared by the present invention contains three transition metal elements, namely iron, cobalt and nickel. Both Co(OH)2 and Ni(OH)2 have good OER activity and conductivity. The graphene quantum dots are electrodeposited on the surface, which increases the active sites and further improves the electron transfer efficiency.

[0018] 3. The graphene quantum dot composite electrolytic water oxygen evolution catalytic material prepared by the present invention has excellent electrocatalytic water evolution activity, and only 238mV is required to drive 100mA / cm 2 The current density was 2.33 W and the Tafel slope was 85 mV / dec, showing high OER electrocatalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the XRD test graph of the graphene quantum dot composite water electrolysis oxygen evolution catalytic material obtained in Example 1;

[0020] Figure 2 This is a SEM image of the graphene quantum dot composite water electrolysis oxygen evolution catalytic material obtained in Example 1;

[0021] Figure 3 The graphene quantum dot composite water electrolysis oxygen evolution catalytic material obtained in Example 1 and Example 2 was subjected to a current density of 100 mA / cm 2 The columnar body with the required overpotential. DETAILED DESCRIPTION

[0022] Specific implementation method 1: The preparation method of the graphene quantum dot composite water electrolysis oxygen evolution catalytic material in this implementation method is implemented according to the following steps:

[0023] Step 1, ultrasonically cleaning the nickel foam (NF) with hydrochloric acid, acetone, anhydrous ethanol, and deionized water in sequence, and obtaining the cleaned nickel foam after drying;

[0024] Step 2: ultrasonically disperse graphene oxide in deionized water, add 30% H2O2 by mass, heat and reflux for 15 to 20 hours, and then dialyze through a 3500Da dialysis bag to obtain a graphene quantum dot (GODs) solution;

[0025] Step 3, dissolving nickel chloride hexahydrate, ferric nitrate nonahydrate, urea and ammonium fluoride in deionized water to obtain a reaction solution, placing the cleaned nickel foam in the reaction solution, and performing a hydrothermal reaction at a temperature of 120 to 150° C. for 6 to 10 hours to obtain a nickel foam loaded with Fe-Ni(OH)2;

[0026] Step 4: placing the nickel foam loaded with Fe-Ni(OH)2 in a Co(OH)2 aqueous solution, and using a three-electrode system to perform constant potential electrodeposition at -0.7 to -0.9 V to obtain Co(OH)2-Ni(OH)2 / nickel foam;

[0027] Step 5: immerse Co(OH)2-Ni(OH)2 / nickel foam as a working electrode in a graphene quantum dot solution, perform electrodeposition in a scanning potential window of 0V to 1.0V using cyclic voltammetry, and obtain a graphene quantum dot composite electrolytic water oxygen evolution catalytic material after washing and drying;

[0028] The molar ratio of nickel chloride hexahydrate to ferric nitrate nonahydrate in the reaction solution of step 3 is (8-15):(1-4).

[0029] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that the ultrasonic cleaning time in step 1 is 10 to 20 minutes.

[0030] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that the dialysis treatment time in step two is 45 to 50 hours.

[0031] Specific implementation method 4: This implementation method is different from any one of specific implementation methods 1 to 3 in that the concentration of the graphene quantum dot solution in step 2 is 0.8 to 2 mg / L.

[0032] Specific implementation mode 5: This implementation mode is different from any one of specific implementation modes 1 to 4 in that the hydrothermal reaction in step 3 is carried out at a temperature of 120° C. for 8 hours.

[0033] Specific embodiment 6: This embodiment is different from any one of specific embodiments 1 to 5 in that in step 3, the molar ratio of nickel chloride hexahydrate to ferric nitrate nonahydrate is controlled to be (10-12):(2-4).

[0034] In this embodiment, the optimal molar ratio of nickel chloride hexahydrate to ferric nitrate nonahydrate is controlled to be 3 to 4:1.

[0035] Specific embodiment seven: This embodiment is different from any one of specific embodiments one to six in that the concentration of the Co(OH)2 aqueous solution in step four is 0.6 to 0.9 mol / L.

[0036] In this embodiment, the concentration of the Co(OH)2 aqueous solution is preferably 0.8 mol / L.

[0037] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that cyclic voltammetry is used in step five, with Ag / AgCl as the reference electrode and a Pt sheet as the counter electrode.

[0038] Specific embodiment 9: This embodiment is different from any one of specific embodiments 1 to 8 in that in step 5, the electrodeposition is performed in a scanning potential window of 0V to 1.0V, the scanning rate is controlled to be 20 to 30 mV / s, and the continuous scanning cycle is 50 to 80 turns.

[0039] Embodiment 1: The preparation method of the graphene quantum dot composite water electrolysis oxygen evolution catalytic material of this embodiment is implemented according to the following steps:

[0040] Step 1, using hydrochloric acid, acetone, anhydrous ethanol, and deionized water to ultrasonically clean the nickel foam (NF) for 15 minutes each, and drying to obtain a cleaned nickel foam substrate;

[0041] Step 2: ultrasonically disperse 100 mg of graphene oxide in 15 mL of deionized water, add 12 mL of 30% H2O2, heat to reflux for 20 h, and then dialyze through a 3500 Da dialysis bag for 48 h to obtain a graphene quantum dot (GODs) solution with a concentration of 1.2 mg / L;

[0042] Step 3, dissolving nickel chloride hexahydrate, ferric nitrate nonahydrate, urea and ammonium fluoride in deionized water to obtain a reaction solution, placing the cleaned nickel foam in the reaction solution, and performing a hydrothermal reaction at a temperature of 120° C. for 8 hours to obtain a nickel foam loaded with Fe-Ni(OH)2;

[0043] Step 4: Place the nickel foam loaded with Fe-Ni(OH)2 in a 0.8 mol / L Co(OH)2 aqueous solution containing 0.08 mol / L NaNO3, and use a three-electrode system to perform constant potential electrodeposition at -0.8 V to obtain Co(OH)2-Ni(OH)2 / nickel foam;

[0044] Step 5: Using Co(OH)2-Ni(OH)2 / nickel foam as a working electrode and immersing it in a graphene quantum dot solution, using Ag / AgCl as a reference electrode and a Pt sheet as a counter electrode, using cyclic voltammetry to perform electrodeposition in a scanning potential window of 0V to 1.0V, controlling the scanning rate to 20mV / s, and performing continuous scanning cycles for 60 cycles, and obtaining a graphene quantum dot composite electrolytic water oxygen evolution catalytic material after washing and drying (drying temperature is 60°C);

[0045] The molar concentration of nickel chloride hexahydrate in the reaction solution of step 3 is 0.05 mol / L, and the molar concentration of ferric nitrate nonahydrate is 0.013 mol / L.

[0046] This embodiment optimizes the ratio of the three elements of iron, cobalt and nickel in the graphene quantum dot composite water electrolysis and oxygen evolution catalytic material.

[0047] The graphene quantum dot composite water electrolysis oxygen evolution catalytic material prepared in this embodiment is a GODs composite Co(OH)2-Ni(OH)2 / nickel foam material, and graphene quantum dots are loaded on the Co(OH)2-Ni(OH)2 / nickel foam electrode.

[0048] Embodiment 2: The preparation method of the graphene quantum dot composite water electrolysis oxygen evolution catalytic material of this embodiment is implemented according to the following steps:

[0049] Step 1, using hydrochloric acid, acetone, anhydrous ethanol, and deionized water to ultrasonically clean the nickel foam (NF) for 15 minutes each, and drying to obtain a cleaned nickel foam substrate;

[0050] Step 2: ultrasonically disperse 100 mg of graphene oxide in 15 mL of deionized water, add 12 mL of 30% H2O2, heat to reflux for 20 h, and then dialyze through a 3500 Da dialysis bag for 48 h to obtain a graphene quantum dot (GODs) solution with a concentration of 1.2 mg / L;

[0051] Step 3, dissolving nickel chloride hexahydrate, ferric nitrate nonahydrate, urea and ammonium fluoride in deionized water to obtain a reaction solution, placing the cleaned nickel foam in the reaction solution, and subjecting the reaction to a hydrothermal reaction at 120° C. for 8 h to obtain nickel foam loaded with Fe-Ni(OH)2, wherein the molar concentration of nickel chloride hexahydrate in the reaction solution is 0.085 mol / L, and the molar concentration of ferric nitrate nonahydrate is 0.013 mol / L;

[0052] Step 4: Place the nickel foam loaded with Fe-Ni(OH)2 in a 0.7 mol / L Co(OH)2 aqueous solution containing 0.08 mol / L NaNO3, and use a three-electrode system to perform constant potential electrodeposition at -0.8 V to obtain Co(OH)2-Ni(OH)2 / nickel foam;

[0053] Step 5. Use Co(OH)2-Ni(OH)2 / nickel foam as the working electrode and immerse it in the graphene quantum dot solution. Use Ag / AgCl as the reference electrode and the Pt sheet as the counter electrode. Use cyclic voltammetry to perform electrodeposition in a scanning potential window of 0V to 1.0V. Control the scanning rate to 20mV / s and perform continuous scanning for 30 cycles. After washing and drying (drying temperature is 60°C), a graphene quantum dot composite electrolytic water oxygen evolution catalytic material is obtained.

[0054] The electrochemical performance of the graphene quantum dot composite water electrolysis oxygen evolution catalytic material prepared in the example was tested:

[0055] The OER performance of the graphene quantum dot composite water electrolysis oxygen evolution catalytic material prepared in Example 1 was tested under the conditions of a three-electrode system in a 1 mol / L alkaline solution. According to the linear sweep voltammetry test, only 238 mV was required to drive 100 mA / cm 2 The current density of the graphene quantum dot composite electrolysis water oxygen evolution catalytic material prepared in the second embodiment requires 263mV to drive 100mA / cm 2 After 15 hours of constant potential (1.5V) stability test in 1 mol / L alkaline solution, the current density of the graphene quantum dot composite water electrolysis oxygen evolution catalytic material prepared in Example 1 decayed to 97.5% of the initial current density.

[0056] The Tafel slope reflects the reaction rate and kinetic performance of the electrocatalyst. After testing, the Tafel slope of the graphene quantum dot composite water electrolysis and oxygen evolution catalytic material obtained in Example 1 is 85mV / dec. The Tafel slope is small, reflecting that this graphene quantum dot composite water electrolysis and oxygen evolution catalytic material has faster reaction kinetics and exhibits excellent OER electrocatalytic performance.

Claims

1. A method for preparing a graphene quantum dot composite water electrolysis oxygen evolution catalytic material, characterized in that The preparation method of the graphene quantum dot composite water electrolysis oxygen evolution catalytic material is achieved by the following steps: Step 1, ultrasonically cleaning the nickel foam using hydrochloric acid, acetone, anhydrous ethanol, and deionized water in sequence, and drying to obtain the cleaned nickel foam; Step 2: ultrasonically disperse graphene oxide in deionized water, add 30% H2O2 by mass, heat and reflux for 15 to 20 hours, and then dialyze through a 3500Da dialysis bag to obtain a graphene quantum dot solution; Step 3, dissolving nickel chloride hexahydrate, ferric nitrate nonahydrate, urea and ammonium fluoride in deionized water to obtain a reaction solution, placing the cleaned nickel foam in the reaction solution, and performing a hydrothermal reaction at a temperature of 120 to 150° C. for 6 to 10 hours to obtain a nickel foam loaded with Fe-Ni(OH)2; Step 4: placing the nickel foam loaded with Fe-Ni(OH)2 in a Co(OH)2 aqueous solution, and using a three-electrode system to perform constant potential electrodeposition at -0.7 to -0.9 V to obtain Co(OH)2-Ni(OH)2 / nickel foam; Step 5: immerse Co(OH)2-Ni(OH)2 / nickel foam as a working electrode in a graphene quantum dot solution, perform electrodeposition in a scanning potential window of 0V to 1.0V using cyclic voltammetry, and obtain a graphene quantum dot composite electrolytic water oxygen evolution catalytic material after washing and drying; The molar ratio of nickel chloride hexahydrate to ferric nitrate nonahydrate in the reaction solution of step 3 is (8-15):(1-4).

2. The method for preparing the graphene quantum dot composite water electrolysis oxygen evolution catalytic material according to claim 1, characterized in that The ultrasonic cleaning time in step 1 is 10 to 20 minutes each time.

3. The method for preparing the graphene quantum dot composite water electrolysis oxygen evolution catalytic material according to claim 1, characterized in that The dialysis treatment time in step 2 is 45 to 50 hours.

4. The method for preparing the graphene quantum dot composite water electrolysis oxygen evolution catalytic material according to claim 1, characterized in that The concentration of the graphene quantum dot solution in step 2 is 0.8-2 mg / L.

5. The method for preparing the graphene quantum dot composite water electrolysis oxygen evolution catalytic material according to claim 1, characterized in that In step 3, the hydrothermal reaction is carried out at 120° C. for 8 h.

6. The method for preparing the graphene quantum dot composite water electrolysis oxygen evolution catalytic material according to claim 1, characterized in that In step 3, the molar ratio of nickel chloride hexahydrate to ferric nitrate nonahydrate is controlled to be (10-12):(2-4).

7. The method for preparing the graphene quantum dot composite water electrolysis oxygen evolution catalytic material according to claim 1, characterized in that The concentration of the Co(OH)2 aqueous solution in step 4 is 0.6-0.9 mol / L.

8. The method for preparing the graphene quantum dot composite water electrolysis oxygen evolution catalytic material according to claim 1, characterized in that In step five, cyclic voltammetry is used, with Ag / AgCl as the reference electrode and Pt sheet as the counter electrode.

9. The method for preparing the graphene quantum dot composite water electrolysis oxygen evolution catalytic material according to claim 1, characterized in that In step 5, the electrodeposition is carried out in a scanning potential window of 0V to 1.0V, the scanning rate is controlled to be 20 to 30mV / s, and the continuous scanning cycle is 50 to 80 times.

10. The use of the graphene quantum dot composite water electrolysis oxygen evolution catalytic material prepared as claimed in claim 1, characterized in that The graphene quantum dot composite water electrolysis oxygen evolution catalytic material is used as an OER electrocatalyst in the electrocatalytic water decomposition reaction.

Citation Information

Patent Citations

  • Preparation method for graphene quantum dot / SnS2 nano-sheet composite photocatalyst

    CN106994355A

  • Graphene-coated sulfurized nickel-cobalt-iron trimetal catalyst and preparation method thereof

    CN113529100A

  • Iron-doped nickel hydroxide composite nickel selenide material as well as preparation method and application thereof

    CN115928135A

  • Preparation method and application of nickel hydroxide coated MnOOH / foamed nickel oxygen evolution catalytic material

    CN117431574A

  • Ultrathin NiFe LDH nanosheet array, composite nanosheet array and preparation method of ultrathin NiFe LDH nanosheet array

    CN118581508A